Analisis Kedudukan Sejarah dalam Studi Hadis dan Ilmu Hadis - Ainun Nuriyah R. S, Zaahidah Aufaa A, Nurwadjah Ahmad, Dendi Yuda S (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2025)
This article aims to narrate the position of history in the science of hadith and hadith studies. Hadith is historical evidence of the journey of the Prophet during his life, from the time of prophethood to his death on 11 Hijri. Everything contained in the hadith can be one of the historical sources that are included in primary sources or direct sources. Between the science of hadith and the science of history, there is a relationship that connects each other, with its function to understand past events in the context of Islam during the time of the Prophet Muhammad. The two sciences complement each other in reconstructing important events that occurred during the life of the Prophet Muhammad. As for the science of hadith, historical studies are required to ensure the authenticity of the sanad (chain of narration) and matan (content of the hadith narration). Understanding the relationship between history and the science of hadith requires an in-depth study of the basic concepts of both. It is necessary to describe the meaning of history and hadith, as well as the history of the development of the science of hadith and the recording of hadith. Keywords: Hadith, History, Prophet Muhammad